Early Childhood In The Age Of Digital Overstimulation: A Critical Analysis Of Character Development Gaps And Integrative Pedagogical Responses - Indah Tri Widiana; Alif Mudiono; Eny Nur Aisyah (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Digital overstimulation has emerged as a critical concern in early childhood education, characterized by excessive screen exposure, rapid and repetitive stimuli, and predominantly passive media consumption patterns. These conditions have altered the quality of children’s learning experiences and raised important questions regarding their implications for developmental outcomes and character formation. This study aims to examine the relationship between digital overstimulation and disparities in character development, as well as to formulate an integrative pedagogical response for young children. The research adopts a qualitative approach, employing a conceptual paper design supported by an integrative review method. Data were collected through systematic searches of reputable academic databases and analyzed using thematic analysis and conceptual synthesis techniques. The findings indicate that high levels of digital exposure are associated with reduced self-regulation, diminished attention span, weakened social interaction, and delayed language development. These effects are estimated to affect approximately 30–65% of children who engage in intensive digital media use. Furthermore, the study identifies noticeable gaps in character development, particularly in areas such as self-control, empathy, and independence. These outcomes are influenced by both the quality of digital media engagement and the extent of adult involvement. This research contributes to the development of an integrative pedagogical framework that emphasizes meaningful interaction, guided digital usage, and a balanced range of learning experiences to support holistic child development in the digital era.